Evaluating the role of pathogenic dementia variants in posterior cortical atrophy - Carrasquillo, Minerva; Barber, Imelda S.; Lincoln, Sarah J.; Murray, Melissa E.; Camsari, Gamze Balci; Khan, Qurat ul Ain; Nguyen, Thuy; Ma, Li; Bisceglio, Gina D.; Crook, Julia E.; Younkin, Steven G.; Dickson, Dennis W.; et al. (Elsevier, 2016)
Posterior cortical atrophy (PCA) is an understudied visual impairment syndrome most often due to “posterior Alzheimer's disease (AD)” pathology. Case studies detected mutations in PSEN1, PSEN2, GRN, MAPT, and PRNP in subjects with clinical PCA. To detect the frequency and spectrum of mutations in known dementia genes in PCA, we screened 124 European-American subjects with clinical PCA (n = 67) or posterior AD neuropathology (n = 57) for variants in genes implicated in AD, frontotemporal dementia, and prion disease using NeuroX, a customized exome array. Frequencies in PCA of the variants annotated as pathogenic or potentially pathogenic were compared against ∼4300 European-American population controls from the NHLBI Exome Sequencing Project. We identified 2 rare variants not previously reported in PCA, TREM2 Arg47His, and PSEN2 Ser130Leu. No other pathogenic or potentially pathogenic variants were detected in the screened dementia genes. In this first systematic variant screen of a PCA cohort, we report 2 rare mutations in TREM2 and PSEN2, validate our previously reported APOE ε4 association, and demonstrate the utility of NeuroX.